Regioselective Palladium-Catalyzed Cross-Coupling Reactions of 2,4,7-Trichloroquinazoline - Wipf, Peter (2010)
The regioselective palladium-catalyzed cross-coupling reactions of 2,4,7-trichloroquinazoline with various aryl- and heteroarylboronic acids are reported. An efficient, sequential strategy was developed that provides access to novel, functionalized heterocycles.